The influence of changes in the average effective rates of income tax article 21 on the effectiveness of taxpayer satisfaction and loyalty at KPP Pratama Gresik - Hidayah, Fatwatus; Kurniawan, Fitri Ahmad (Educoretax, 2024)
Tax regulations undergo dynamic changes in every period of time. This also occurs in tax regulations for income tax 21 (PPh 21), one of which is individual income such as TER (average effective rate). With the average effective rate, individual taxpayers can now find their non-taxable income (PTKP) value more easily. This study intends to examine the effect of changes in the average effective rate (TER) on taxpayers' perceptions of their satisfaction and loyalty at KPP Pratama Gresik. A quantitative approach is applied in this study, with primary data collected through questionnaires distributed to individual taxpayers at KPP Pratama Gresik. The population of this study is all individual taxpayers at KPP Pratama Gresik, with a sample of 100 respondents obtained through accidental sampling technique. Data analysis shows that changes in TER (average effective rate) have a positive influence on the level of taxpayer satisfaction at KPP Pratama Gresik, in accordance with the first hypothesis. The results also support the second hypothesis which states that changes in TER (average effective rate) have a positive influence on taxpayer loyalty at KPP Pratama Gresik. The research contribution for the Directorate General of Taxes (DGT) is that in terms of increasing the tax revenue target, it must be driven by a sense of satisfaction and loyalty of taxpayers in paying taxes.